2008
DOI: 10.1007/bf02982673
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial on early physiotherapy intervention versus usual care in acute car unit for elderly: Potential benefits in light of dietary intakes

Abstract: Physical intervention programs should be proposed according to nutritional intakes with the aim of preventing illness induced disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 27 publications
1
68
0
Order By: Relevance
“…Some studies have reported minor changes in handgrip strength (Englund et al, 2005;Figueroa et al, 2011;Geirsdottir et al, 2012;Pereira et al, 2012;Sarti et al, 2013;Skelton et al, 1995;Straight et al, 2012;Tsourlou et al, 2006), but the majority of studies have not been able to detect significant differences in handgrip strength in response to traditional whole-body resistance-type exercise training programs in older people (Blanc-Bisson et al, 2008;Bunout et al, 2004;de Vreede et al, 2005;Gudlaugsson et al, 2012;Leenders et al, 2013;Park et al, 2012;Rhodes et al, 2000;Seco et al, 2013;SerraRexach et al, 2011;Winters-Stone et al, 2012;Woo et al, 2007. An overview of these studies is given in Table 3. The apparent discrepancy among those studies might be due to variety in designs.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have reported minor changes in handgrip strength (Englund et al, 2005;Figueroa et al, 2011;Geirsdottir et al, 2012;Pereira et al, 2012;Sarti et al, 2013;Skelton et al, 1995;Straight et al, 2012;Tsourlou et al, 2006), but the majority of studies have not been able to detect significant differences in handgrip strength in response to traditional whole-body resistance-type exercise training programs in older people (Blanc-Bisson et al, 2008;Bunout et al, 2004;de Vreede et al, 2005;Gudlaugsson et al, 2012;Leenders et al, 2013;Park et al, 2012;Rhodes et al, 2000;Seco et al, 2013;SerraRexach et al, 2011;Winters-Stone et al, 2012;Woo et al, 2007. An overview of these studies is given in Table 3. The apparent discrepancy among those studies might be due to variety in designs.…”
Section: Discussionmentioning
confidence: 95%
“…The living situation of the patients before they were admitted to the hospital varied, patients came from nursing homes and other types of institutionalised care or from the community where they lived alone or with family. However, the studies did not include all patients in the intervention, reasons for exclusion were medical instability [18,22,23], need for specialized care [17,19,22,24], living in nursing homes [19,20,22,23,25,26,28], small survival chance or need for palliative care [18,22,23,25,28], and being diagnosed with an illness causing functional impairment [18,23,28]. Overall, there was a great heterogeneity among the participants between the different studies.…”
Section: Resultsmentioning
confidence: 99%
“…45 Early physiotherapy during hospitalization for acute disease has been shown to improve ADL recovery in older patients who were bed-ridden at admission. 46 The intervention tested in the randomized controlled trial by Blanc-Bisson et al, 46 consisted of physiotherapy sessions compared with usual care, started at day 1 or 2, in half-hour sessions twice daily, until patient walking abilities were recovered. Lower limb strength was reinforced in the bed using dynamic work, against the foot of the bed or the hand of the physiotherapist, with the knee flexed at 30°, and moving the pelvis to the left and to the right with 10 repetitions for each movement.…”
Section: Prevention Of Functional Loss In Hospital and Loss Of Autonomentioning
confidence: 99%